Effect of Shift Work System (3 Groups) on Employee Motivation,Compensation and Performance At PT. Prima Alam Gemilang in Bombana, Southeast Sulawesi - Muhammad Saing Thahir (Scientia Integritas Utama, 2022)
This study aims to determine the effect of the Shift Work System (3 Groups) both directly and indirectly, positively and significantly on the motivation, compensation and performance of employees at PT. Prima Alam Gemilang (Sugar Factory Bombana). The research method used in this research is descriptive quantitative, which is a method that uses quantitative data collection through questionnaires by setting a score for each answer to the questionnaire, then the data is processed through various formulations, namely descriptive statistics, then testing instruments in the form of validity tests and reliability test, and so on describes the results of the analysis output processed with SPSS. The formulation of the problem and the research hypothesis can be shown that the shift work system (3 groups) has a direct and indirect, positive and significant effect on motivation, compensation and employee performance at PT. Prima Alam Gemilang, where this can be described through work shift indicators which consist of: Shift Duration, Number of Workers/Teams, Rotation Speed, Holidays/Rest, Shift Schedule Regularity which on average the perception of respondents gives an assessment of 4.49 (very agree). : Wages, Incentives, Allowances, Salaries, Pensions where the average perception of respondents gives an assessment of 4.63 (strongly agree), and Employee Performance Indicators consisting of: Quality, Quantity, Timeliness, Effectiveness, Independence, Work Commitment the average perception of respondents gives an assessment of 4.45 (strongly agree) Shift Work System Variables (3 Groups) have a direct and indirect, positive and significant influence on the motivation, compensation and performance of employees at PT. Prima Alam Gemilang but for the company's long-term operations it is necessary to evaluate the model into 4 groups because this trend is only temporary which is heavily influenced by the average age of workers who are still 20-30 years old and the marital status of workers is still single/not married with the biggest motivation being the focus on meeting physical needs.